The Triple Effect of Carbon Taxation: Rhetoric Versus Reality in Climate Policy - Riyono, Kenley Maccauley; Widianingsih, Luky Patricia (Jurnal Akuntansi, 2025)
This study examines the impact of carbon tax implementation across various sectors on carbon emissions and social welfare, moderated by subsidies and tax liability offsets. The sample consists of 28 countries that implemented a carbon tax in 2023. The analytical method is moderated regression analysis. The results show that the carbon tax significantly negatively affects carbon emissions, even without the interaction of subsidies and tax liability offsets. It is also found that the most effective sectors are transportation, electricity, and heat. Moreover, the carbon tax significantly positively affects social welfare, subsidies, and tax liability offsets interact, particularly in the building sector. These findings reveal that carbon taxes have three benefits for the environment, society, and the economy.